2020
DOI: 10.1038/s41573-020-0068-6
|View full text |Cite|
|
Sign up to set email alerts
|

RAS-targeted therapies: is the undruggable drugged?

Abstract: RAS (KRAS, NRAS and HRAS) is the most frequently mutated gene family in cancers, and, consequently, investigators have sought an effective RAS inhibitor for more than three decades. Even 10 years ago, RAS inhibitors were so elusive that RAS was termed 'undruggable'. Now, with the success of allele-specific covalent inhibitors against the most frequently mutated version of RAS in non-small-cell lung cancer, KRAS G12C , we have the opportunity to evaluate the best therapeutic strategies to treat RAS-driven cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
754
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 739 publications
(763 citation statements)
references
References 266 publications
(290 reference statements)
4
754
0
5
Order By: Relevance
“…Unfortunately, monotherapies targeted to RAS oncogenes have mostly failed following initial response owing to resistance occurring via different mechanisms such as feedback reactivation of RAS-downstream pathways. Nevertheless, substantial advances have been made lately, introducing promising compounds where some are undergoing clinical trials (reviewed in Moore et al 81 ). This includes approaches targeting KRAS G12C oncoproteins or blocking GTP loading of KRAS oncoproteins, which indicate that direct targeting of KRAS might be achievable eventually, even though acquired resistance phenomena against these novel therapies might be inevitable 82 .…”
Section: Clinical Translationmentioning
confidence: 99%
“…Unfortunately, monotherapies targeted to RAS oncogenes have mostly failed following initial response owing to resistance occurring via different mechanisms such as feedback reactivation of RAS-downstream pathways. Nevertheless, substantial advances have been made lately, introducing promising compounds where some are undergoing clinical trials (reviewed in Moore et al 81 ). This includes approaches targeting KRAS G12C oncoproteins or blocking GTP loading of KRAS oncoproteins, which indicate that direct targeting of KRAS might be achievable eventually, even though acquired resistance phenomena against these novel therapies might be inevitable 82 .…”
Section: Clinical Translationmentioning
confidence: 99%
“…Activating mutations in KRAS, NRAS, and HRAS, which encode for members of the RAS family of proteins, occur at high prevalence in many cancer types, particularly subtypes of lung and pancreatic cancers. 115 One of the earliest shRNA screens first focused on identifying genes that may alter RAS activity in the absence of a mutation using modified primary fibroblasts, with enhanced potential to transform. The screen identified the transcription factor PITX1 as a putative suppressor of RAS activity, 116 a finding subsequent studies of hepatocarcinogenesis confirmed.…”
Section: The Ras Oncoprotein Familymentioning
confidence: 99%
“…Research into drugs targeting Ras has made progress (20). Certain research demonstrated that 2,3-dichloro-1,4-naphthoquinone inhibited the growth of N-Ras-mutant melanoma (21), while 2-(2' ,4'-dihydroxyphenyl)-8-hydroxy-1,4-naphthoquinone and 5-hydroxy-2-(2,4-dihydroxyphenyl)naphthalene-1,4-dione inhibited Apc/K-Ras-mutant mouse organoid differentiation capacity (22).…”
Section: The Compound 2-benzylthio-58-dimethoxynaphthalene-14-dionementioning
confidence: 99%